Against the tide (Tell Me Films, 2014)
Since the mid- 1990s, more than 20,000 migrants have died in the Mediterranean attempting to reach Europe. Boats have gone adrift, sinking under the eyes of coast guard ships, surveillance patrols of Frontex and sometimes military buildings. In July 2012, a Euro-African activist coalition called "Boats 4 People" chartered a boat for a solidarity action in order to monitor the border and denounce those responsible for this situation. Activists, lawyers and journalists were on board to sail the migration route the opposite way it is usually crossed by boat-people. This film shares the extraordinary action taken by activists from Africa and Europe - raising awareness, mobilizing public opinion and continuing the struggle for the rights of boat-people.